On multiaxial failure behavior of closed-cell aluminum foams under medium strain rates - Wang, Erdong; Sun, Guangyong; Zheng, Gang; Li, Qing (Thin-walled structures, 2021)
Metal foams are commonly used to withstand impact loading from different directions in real life applications attributable to their superior performance of energy absorption to weight. It has been of special interest to explore the complex yield/failure behavior of metal foams under dynamic impact recently. However, existing studies have mainly focused on crushing behavior under simple quasi-static loading conditions. Hence, this study aims to explore the multiaxial dynamic failure behavior of closed-cell aluminium foams. First, the uniaxial failure behavior of foams with three different apparent densities is experimentally investigated at varying strain rates (10−3-150 s−1) through quasi-static compression and drop weight tests, respectively. It is found that the initial failure strength exhibits evident strain-rate dependency. An empirical relation is established to associate the initial failure strength with relative density and nominal strain rate. Second, the multi-axial failure behavior is characterized based upon the developed microscopic computed tomography (micro-CT) image foam models. It is revealed that at low and medium strain rates, the hardening of the uniaxial failure strength is rate-dependent on the foam cell-wall base material. Under compression-shear and triaxial compression loadings, the initial failure surface in the von Mises - mean stress plane significantly expands with increasing strain rates. After normalized by the uniaxial failure strength at the corresponding strain rates, the failure surface is almost independent of loading or strain rates. The normalized failure surface can be well depicted by an elliptic or a parabolic function. Moreover, with use of suitable plastic Poisson's ratio, the normalized failure surface could be well characterized by Deshpande and Fleck (D&F) model and Miller model. The modified rate-dependent constitutive models are suggested for foam materials subject to quasi-static and dynamic loadings. [Display omitted] •Multiaxial properties of closed-cell Al foams are characterized based upon micro-CT based models.•Rate dependence of foam cell-wall leads to strain-rate sensitivity of the initial failure strength.•The normalized failure surface is independent of strain rate.•The modified Miller and D&F models are proposed with consideration of strain-rate effects.